1997
DOI: 10.1007/s002620050405
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of recurrent glioma with intracavitary alloreactive cytotoxic T lymphocytes and interleukin-2

Abstract: For a single-dose toxicity assessment, five patients with recurrent malignant glioma (ages 29-46 years) were treated with intracavitary alloreactive cytotoxic T lymphocytes (CTL) and interleukin-2 (IL-2). The trial tested the hypothesis that alloreactive CTL, sensitized to the major histocompatibility complex (MHC) proteins of the patient, offer selective, targeted killing of glioma cells that express MHC. Patient lymphocytes, which also express MHC, were irradiated and placed into CellMax artificial capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 0 publications
1
74
0
7
Order By: Relevance
“…Para evitar esta complicación, se han desarrollado diferentes vías de administración 50,91 . En los últimos años se ha propuesto como alternativa la utilización de células programadas genéticamente, para producir la liberación prolongada y mantenida de las sustancias deseadas mediante la transducción de genes de citoquinas 58,107 .…”
Section: Terapia Con Citoquinasunclassified
See 2 more Smart Citations
“…Para evitar esta complicación, se han desarrollado diferentes vías de administración 50,91 . En los últimos años se ha propuesto como alternativa la utilización de células programadas genéticamente, para producir la liberación prolongada y mantenida de las sustancias deseadas mediante la transducción de genes de citoquinas 58,107 .…”
Section: Terapia Con Citoquinasunclassified
“…Se han desarrollado otras vías de administración y se utiliza en múltiples protocolos, tanto como terapia única como en combinación con quimioterapia 91 , o terapias celulares 50 . Más recientemente, se ha publicado el desarrollo de biopolímeros de liberación controlada de esta citoquina 83 , y el desarrollo de células modificadas genéticamente para producirla de manera continuada y prolongada 29 .…”
Section: Terapia Con Citoquinasunclassified
See 1 more Smart Citation
“…IL-2 has also been used in clinical studies with cytotoxic T lymphocytes [43]. Initially, five patients with recurrent glioma were treated with intracavitary CTLs and IL-2.…”
Section: Cytokinesmentioning
confidence: 99%
“…Control patients had a median survival of 13.6 months from their initial diagnosis, with a 2-year survival rate of 20%; for the 31 patients who underwent LAK cell placement during the course of their disease, median survival was 17.5 months and the 2-year survival rate was 31% (p2 = 0.012). However, other studies using LAK cells could not reproduce these encouraging outcomes, and one study reported considerable toxicity [42].IL-2 has also been used in clinical studies with cytotoxic T lymphocytes [43]. Initially, five patients with recurrent glioma were treated with intracavitary CTLs and IL-2.…”
mentioning
confidence: 99%